Sikap Konsumen terhadap Atribut Buah Jeruk Lokal dan Impor di Kota Denpasar - RAHMAWATI, DIANAH UMI; ANTARA, MADE; SURYAWARDANI, I G. A. OKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.3, No.2, April 2014, 2018)
Consumer Attitudes Toward Attributes of Local and Import Orange in Denpasar Efforts to meet the needs of orange fruit to the community is reflected by the number of orange fruit imported into indonesia.Various types of orange on the market will affect consumer attitudes in buying local and imports orange fruit that will increase the competition's heat between local and imports orange fruit in Denpasar. The aims of this study are to determine the consumer attitudes toward orange fruit attributes, knowing the competitiveness of local orange fruit viewed from consumer attitudes toward the attributes of local and imports orange fruit in Denpasar. Data collection was conducted at Badung Market, Kreneng Market, Tiara Dewata Supermarket, Hardy's Supermarket and Moena Fresh Fruit Shop located in Denpasar. Determination of samples by accidental sampling method with the number of samples of 60 respondents. Fishbein shows more positive consumer attitudes toward imported orange fruit attributes than local orange fruit. The overall meaning of imported orange fruit is superior to that of local orange fruit for the tendency of competitiveness of local orange fruit is still lower with imported orange fruit.